Correlates of dysfunctional career thoughts in breast cancer survivors from the Bahamas. Issue 5 (3rd September 2019) - Dames, Levette S.; Ghekiere, Elizabeth; Zalaquett, Carlos P.; Kromrey, Jeffrey D.; Ellerbrock, Cheryl R.; Exum, Herbert; Paxton, Raheem J.
Abstract: Purpose: The purpose of this research was to examine the correlates of dysfunctional career thoughts (DCTs) in a sample of breast cancers survivors. Sample and design: A total of 195 breast cancer survivors from the Bahamas completed a cross-sectional survey. Methods: The Career Thoughts Inventory (CTI) and standard medical and demographic items were administered. Analysis of Variance and logistic regression models were used to examine associations. Findings: Total CTI scores differed by age group, marital status, surgical remedy, and employment prior to diagnosis. The odds of DCT were higher among younger (Odds Ratio [OR] = 4.4), married (OR = 2.4), who were unemployed prior to diagnosis (OR = 3.5). Conclusion: Dysfunctional career thoughts appear to be common in certain breast cancer survivors. Further research is needed to determine whether similar associations are observed in other samples. Implications for Providers: Providers should discuss DCTs after treatment.